2023
DOI: 10.3390/molecules28062700
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Nanocarriers for Topical-Mediated RNAi Strategies for Crop Protection—A Review

Abstract: To fulfil the growing needs of the global population, sustainability in food production must be ensured. Insect pests and pathogens are primarily responsible for one-third of food losses and harmful synthetic pesticides have been applied to protect crops from these pests and other pathogens such as viruses and fungi. An alternative pathogen control mechanism that is more “friendly” to the environment can be developed by externally applying double-stranded RNAs (dsRNAs) to suppress gene expression. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
(114 reference statements)
1
1
0
Order By: Relevance
“…In this respect, we observed that exogenous dsRNAs persist on zucchini leaves for several days (11 dpi), but, even if the quantity of dsRNA molecules provided to the plants is high, only a small amount move systemically; indeed, this translocation occurs within the plant shortly after treatment and is stably maintained. These findings are in line with those previously reported in N. benthamiana [25], tobacco [42] and cucurbits [43] and prompts the need of developing ad hoc nanocarriers able to facilitate the delivery and increase the stability of dsRNAs in the plant [44] and the dsRNA-delivered siRNA production [45].…”
Section: Discussionsupporting
confidence: 90%
“…In this respect, we observed that exogenous dsRNAs persist on zucchini leaves for several days (11 dpi), but, even if the quantity of dsRNA molecules provided to the plants is high, only a small amount move systemically; indeed, this translocation occurs within the plant shortly after treatment and is stably maintained. These findings are in line with those previously reported in N. benthamiana [25], tobacco [42] and cucurbits [43] and prompts the need of developing ad hoc nanocarriers able to facilitate the delivery and increase the stability of dsRNAs in the plant [44] and the dsRNA-delivered siRNA production [45].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, specially designed delivery systems have been especially used with the goal to improve the efficacy of dsRNAs. In particular, recent developments in nanoparticle-mediated carriers for dsRNA delivery include layered double hydroxide, carbon dots, carbon nanotubes, gold nanoparticles, chitosan nanoparticles, silica nanoparticles, liposomes, and cell-penetrating peptides [240].…”
Section: Conclusion: Vsrs and New Directions In Plant Protectionmentioning
confidence: 99%
“…The veterinary applications of nanocarriers are conceptually similar to drug delivery in humans [7]. Nanocontainers also have great agricultural potential for the delivery of nutrients and various agrochemicals including pesticides, herbicides, plant growth regulators, and foreign DNA or RNA in plants [8][9][10] through leaf cuticular or stomatal pathways using foliar spraying methods [11][12][13][14]. Apart from the general use of nanocarriers in the therapy of some disorders and diagnostics, they can also be used for the treatment of some distinctive organ diseases, e.g., eye diseases.…”
Section: Introductionmentioning
confidence: 99%